DIGITAL LEADERSHIP DEVELOPMENT MODEL FOR SCHOOL ADMINISTRATORS OF SAINT GABRIEL’ FOUNDATION IN THAILAND - Suksaen, Kanyarat; Trirat, Pratoomtong (Journal of Buddhist Anthropology, 2021)
The objectives of this research article were 1) to explore the current and desirable states of the digital leadership development model for school administrators of the Saint Gabriel’s Foundation, Thailand; and 2) to propose the digital leadership development model for school administrators of the Saint Gabriel’s Foundation, Thailand. A mixed methods research was employed. A sample group was 16 schools under the Saint Gabriel’s Foundation in Thailand, The research instruments consisted of current and desirable states questionnaire, and model propriety, and feasibility evaluation form. The analysis involved descriptive statistics i.e. mean, and standard deviation; PNI Modified, and content analysis. The findings revealed that the current state of the overall digital leadership development was at a high level ( = 3.65, S.D = 0.62), and the overall desirable condition was at the highest ( = 4.80, S.D = 0.41). The digital leadership development model named digital leadership development model on online and artificial intelligence technology success by coherent vision, convergence, and culture cover four elements: 2.1) Main components consisting of 2.1.1) Coherent vision and communication strategy 2.1.2) Convergence and connect administrators 2.1.3) Culture and center learning digital; 2.2) Development method consisting of 2.2.1) Artificial intelligence through an online system 2.2.2) Online study & certificate 2.2.3) Online self - learning; 2.3) Development objectives consisting of 2.3.1) Purpose 2.3.2) Data collection and coding 2.3.3) Collaboration management; and 2.4) Development goals consisting of 2.4.1) Inspiration 2.4.2) Confidence 2.4.3) Time management 2.4.4) Transformation, and 2.4.5) virtual reality.